Understanding the cost of capital of logistics service providers: an empirical investigation of multiple contingency variables - Kerstin Lampe; Erik Hofmann (Logistics Research, 2014)
The article analyzes the influence of company-, industry- andmarket-related variables on the cost of capital of logistics service providers, as well as on their systematic risk. Financial information has become more and more important in strategic decision making (especially in the international context); in addition of being a measure of performance, the cost of capital is an important variable for logistics service providers in decisions about investing capital and developing the appropriate strategy. In total, financial data on over 700 logistics service providers for a period of 10 years were analyzed applying multiple regression analysis. Our results show that the logistics service industry is rather nonvolatile from an investor's viewpoint. Microeconomic variables significantly influence the cost of capital of logistics service providers, whereas systematic risk is influenced by macroeconomic variables. In both cases, significance is strongly dependent on the services offered and financial structure of the companies, although the headquarters location is irrelevant. Main implication of our study underlines the specific interdependencies of strategic decision making and cost of capital of logistics service providers.As recent researchmade only little efforts in linking the fields of business logistics and corporate finance, we follow a broad research approach to give a first comprehensive overview on this interdisciplinary topic.
Keywords: 650; Cost of capital; Systematic risk; Key financial figures; Logistics service providers; Strategic decisions; Value creation